Mediating Effect of Customer Engagement on the Relations between eWOM, Environmental Concern, and Intention to Purchase Second-hand Clothing among College Students in Yogyakarta - Kristia, Kristia (Jurnal Manajemen Bisnis, 2021)
Research aims: This study examines the direct and indirect effects of eWOM and environmental concerns on second-hand clothing purchase intention. However, on the intervening variable, this study used customer engagement.Design/Methodology/Approach: This quantitative research distributed questionnaires to 222 college students aged 18-24 years who were interested in and were familiar with the concept of using second-hand clothes, who were also lived in Yogyakarta. The questionnaire results were then processed utilizing the structural equation modeling-partial least square (SEM-PLS) technique.Research findings: This study’s findings showed that consumer engagement had a full mediating impact between eWOM and intention in buying second-hand clothes. However, it only partially affected the relationship between environmental concern and the intention to purchase used clothes.Theoretical contribution/Originality: Previous studies have investigated the relationship between eWOM and purchase intention through customer engagement as a mediating variable, but little literature involves environmental concerns in the model. Another contribution is the findings that revealed that eWOM could not influence students' purchase intention in second-hand clothes without the involvement of customer engagement.Practitioner/Policy implication: The author suggests that second-hand clothes sellers and non-profit organizations could increase young people's involvement in making environmentally friendly consumption in the form of buying used clothes by increasing consumer engagement.Research limitation/Implication: This research's limitations include the limited variables studied and the characteristics of respondents who only focused on generation Z, especially students in Yogyakarta.